A Fake Hadith And How to Research Them in Digital Space (Journal Intellectual Sufism Research (JISR), 2024)
This article examines the understanding of false hadith and how to research it in the digital space. Along with the rapid development of technology, hadith can be found in various digital media. However, not everyone is able to be careful in distributing hadith. It is not uncommon for wise words to be claimed as hadith when in fact they are false. This kind of phenomenon is certainly a concern, which is why this article was written. The method used in this research is a qualitative method, namely utilizing references in the form of books, journals, and other research. The results of this study show that false hadith are words, actions, and provisions that are made up and then attributed to the Prophet. Contemporary scholars say that the first forgery of hadith occurred during the time of Caliph Ali. Nowadays, hadith research can be done on digital media such as smartphones. Among digital media features in smartphone that can be utilized are the hadith application al-Jami' kutub al-Tis`ah and the dorar.net website. If the hadith being studied is indicated as a fake hadith, it certainly cannot be found in the application.